2013
DOI: 10.1037/a0033413
|View full text |Cite
|
Sign up to set email alerts
|

Suppression and interpersonal harmony: A cross-cultural comparison between Chinese and European Americans.

Abstract: Based on Markus and Kitayama's (1991) theory, this study was conducted to examine whether the association between emotional suppression and interpersonal harmony would be moderated by cultural group (i.e., Chinese and European Americans) and an Asian cultural value (i.e., emotional self-control). A total of 451 college students (205 Chinese and 246 European Americans) participated in this study. As expected, results indicated that the association between emotional suppression and interpersonal harmony was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(180 citation statements)
references
References 41 publications
(88 reference statements)
4
174
2
Order By: Relevance
“…A study of 23 countries revealed that cultures that valued embeddedness, hierarchy, and were future-oriented reported engaging in greater emotion suppression than cultures valuing individualism, egalitarianism, and affective autonomy (Matsumoto et al, 2008). A similar study recording impressions of Taiwanese Chinese and European Americans indicated that Taiwanese Chinese engage in more suppression to maintain interpersonal harmony compared to their European American counterparts (Wei, Su, Carrera, & Lin, 2013). These studies support the general consensus that Asian cultures believe that self-expression may 'disturb social harmony' leading to constant engagement in emotion regulation (Markus & Kitayama, 1991).…”
Section: The Singapore Contextmentioning
confidence: 93%
See 2 more Smart Citations
“…A study of 23 countries revealed that cultures that valued embeddedness, hierarchy, and were future-oriented reported engaging in greater emotion suppression than cultures valuing individualism, egalitarianism, and affective autonomy (Matsumoto et al, 2008). A similar study recording impressions of Taiwanese Chinese and European Americans indicated that Taiwanese Chinese engage in more suppression to maintain interpersonal harmony compared to their European American counterparts (Wei, Su, Carrera, & Lin, 2013). These studies support the general consensus that Asian cultures believe that self-expression may 'disturb social harmony' leading to constant engagement in emotion regulation (Markus & Kitayama, 1991).…”
Section: The Singapore Contextmentioning
confidence: 93%
“…In general, individualistic cultures promote primacy of individual needs, and individuals are encouraged to be authentic and open with their expression (Butler et al, 2007). Collectivist cultures value emotion suppression (Matsumoto et al, 2008), generally have more rules for expression management, and are more sensitive to others around them when expressing emotion, especially negative emotions (Butler et al, 2007;Safdar et al, 2009;Wei et al, 2013). Thus, extended to expression of positive and negative emotions we predict:…”
Section: The Singapore Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…East Asian cultures generally value emotional expression less and suppression more than Western cultures (Butler, Lee, & Gross, 2007;Ford & Mauss, 2015;Su, Wei, & Tsai, 2014;Tsai & Clobert, in press;Wei et al, 2013). The study of Eid and Diener (2001) was focused on desired and undesired emotions in the United States, Australia, Taiwan and China.…”
Section: Emotion-related Valuesmentioning
confidence: 99%
“…Recent empirical evidence has shown that cultures vary in emotion-related values (e.g., Su, Wei, & Tsai, 2014;Tsai & Clobert, in press;Wei, Su, Carrera, Lin, & Yi, 2013) as well as in complexity and differentiation of display rules, i.e. norms for emotional expression (Matsumoto, Yoo, & Fontaine, 2009).…”
Section: Introductionmentioning
confidence: 99%